Transformasi Sampah Menjadi Peluang Usaha: Pelatihan Ekonomi Kreatif bagi Perempuan Morowali - Rofiah, Chusnul; Idham, Idham; Rapitasari , Diana (Unity Academy, 2025)
This community service program aims to empower women from Morowali Regency through intensive training on transforming waste into economically valuable products within the framework of the creative economy. The activity was held in Surabaya for five days, involving 80 participants. The training materials covered waste sorting, recycling into handicraft products, pricing strategies, packaging, and digital marketing. The program was delivered through collaboration between lecturers from three universities and two waste management practitioners. Based on the evaluation, participants showed significant improvements in theoretical understanding (with 20% rated as excellent and 33% as good) as well as practical skills in product creation. This program not only enhanced technical skills but also fostered entrepreneurial spirit and environmental awareness. The results indicated that women have strong potential as agents of change in generating economic opportunities from household waste.